Factor affecting students’ performance in Web-Based Learning (WBL) during the COVID-19 pandemic among degree students at UiTM Kampus Seremban 3, Negeri Sembilan / Nur Syazwani Yahya and Wan Maryam Wan Mohammad - Yahya, Nur Syazwani; Wan Mohammad, Wan Maryam (2022)
The purpose of this paper is to investigate the factors that influence students' performance in Web-Based Learning (WBL) at UiTM Kampus Seremban 3 during the COVID-19 Pandemic. The participants in this study are degree students. In order to collect data for the study, researchers utilized an online structured questionnaire to collect 348 responses from students. Researchers have also used quantitative methods to analyze data. The research aims to find out the relationship between learning attitudes, learning anxiety, and learning motivation to student performance in web-based learning. According to the findings, a constructive connection exists between student performance and factors including learning attitudes, learning anxiety, and learning motivation. In this study, researchers have prepared some limitations for future research.